Morphology and sediments of ice-dammed lake after its outburst, West Greenland - Česnulevičius, Algimantas; Šeirienė, Vaida; Kazakauskas, Vaidotas; Baltrūnas, Valentinas; Šinkūnas, Petras; Karmaza, Bronislavas (Geologija, 2009)
Formation of glaciolacustrine basins during glacier recession is predetermined by abundance of supraglacial, inglacial and subglacial waters. Replenishment of glaciolacustrine basins is followed by their sudden drainage associated with glacier outbursts and melting of buried ice in the areas of end moraines, or capture of glaciofluvial streams. The outburst flood that appeared on August 31, 2007 in the periphery of the Russell glacier (West Greenland) caused a rapid drainage of an ice-dammed lake, which exposed a large part of the bottom and the slopes of the basin. The water level in the basin during the drainage subsided by 55 m, and in 11 hours of outburst flood 20 900 000 m3 of water escaped from the basin. The exposed bottom of the glaciolacustrine basin allowed evaluating the sediment complexes. The impact of glaciofluvial stream on the forms of relief was established as well.